Coexistence of adjacent vacancy-ordered and eutectic phases in Al–Cu–Ni alloys. (2nd November 2018) - Maity, Shubhadeep; Chanda, Dipak Kr; Ramasamy, Parthiban; Show, Bijay Kumar; Eckert, Jürgen; Bera, Supriya
ABSTRACT: Copper-mould-cast Al–Cu–Ni alloys show adjacent coexistence of in situ grown ordered and eutectic phases. A bimodal microstructure of α–Al and eutectic α-Al+θ-Al2 Cu phases with length-scale hierarchy evolves during solidification. Microstructural analysis through Transmission Electron Microscopy (TEM) and Scanning Electron Microscopy (SEM) shows the presence of Vacancy-ordered phases (VOPs) with different morphologies in two different compositions.